Dealing with climate change through understanding tropical ocean-atmosphere climate interactions and their impacts on marine ecosystems. - Zinke, Jens; McGregor, H.; Abram, N.; Lough, J.; Gagan, M.; O'Leary, Mick; McCulloch, M.; Webster, J.; Woodroffe, C. (Australasian Quarternary Association, Inc., 2015)
Australian scientists are world leaders in developing robust palaeo-environmental reconstructions from coral archives, relevant for understanding Australian climate extremes. The key issues for advancing this field are the need for high-resolution marine paleoclimate records to place the present in the context of past natural climate and sea level change, and to understand the impact of those changes on marine ecosystems. We call for sustained investment in paleoclimate science, infrastructure, and personnel to advance these critical areas of research.